Genetic parameter estimates in Sabi sheep - Matika, O.; Wyk, J.B. van; Erasmus, G.J.; Baker, R.L. (Elsevier, 2003)
Genetic parameters for growth traits in Sabi sheep were estimated using from data records of 4123 lambs from 130 sires and 1131 dams collected between 1984 and 1994. Reproduction traits and lamb survival to weaning were analysed fitting a sire threshold model. The direct additive contribution to birth weight, 30-day weight, 60-day weight, weaning weight (WW), preweaning average daily gain (ADG), 12-months weight, 18-months weight and Kleiber ratio (KL=ADG to weaning/WW0.75) was 0.25, 0.11, 0.13, 0.13, 0.17, 0.26, 0.37 and 0.08, respectively. The direct heritability for slaughter, hot and cold carcass weight, total litter weight weaned, mating and postpartum weight and ewe weight at weaning of lamb was 0.27, 0.18, 0.18, 0.12, 0.58, 0.53 and 0.67, respectively. Maternal heritabilty declined from 0.12 at birth to 0.06 at 60 days of age and was negligible thereafter. The maternal permanent environmental component due to the dam contributed 3-15% of the total phenotypic variances for all the traits under consideration. Genetic progress is possible for all the growth, carcass and ewe traits considered in this study. The heritabilty estimates for reproduction traits were low, viz 0.02, 0.06, 0.04, 0.02 and 0.04 for fertility (whether a ewe lamb or not; 0 or 1); reproductive rate (number of lambs born to a ewe mated; 0, 1 or 2); number of lambs weaned to a ewe lambing (0, 1 or 2); number of lambs weaned to a ewe exposed (0, 1 or 2), and lamb survival rate (whether a lamb born alive, was dead or alive at weaning). Though slow genetic progress is possible with all reproduction and survival traits, it would be more efficient to select for prolificacy (number of lambs born to a ewe that lambed; 1 or 2) (h2=0.26) but guarding against a higher lamb mortality.